2018
DOI: 10.3389/fneur.2018.00995
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Stratification of Epileptogenic Lesions in Elderly With New Onset Seizures

Abstract: Objective: To evaluate prospectively the frequency of epileptogenic lesions in a consecutive cohort of elderly patients presenting with new onset unprovoked seizures, and who underwent a complete evaluation including dedicated epilepsy protocol MRI.Methods and materials: We included all consecutive patients 60 years or older who participated in a prospective study on new onset epilepsy. The work-up included the acquisition of a dedicated epilepsy protocol MRI and a 3 h video/EEG recording. We evaluated the fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 46 publications
(52 reference statements)
3
7
1
Order By: Relevance
“…6 The EEG and brain imaging in older people reveal nonspecific findings more often than in younger patients with epilepsy. 19 Yield of interictal EEG in older patients with new-onset epilepsy is low (21%-37%), 20,21 an observation confirmed in our study (30.8%). In comparison, 52% had epileptiform abnormalities on their first EEG in a cohort of 441 children and young adults with incident epilepsy.…”
Section: Discussionsupporting
confidence: 85%
“…6 The EEG and brain imaging in older people reveal nonspecific findings more often than in younger patients with epilepsy. 19 Yield of interictal EEG in older patients with new-onset epilepsy is low (21%-37%), 20,21 an observation confirmed in our study (30.8%). In comparison, 52% had epileptiform abnormalities on their first EEG in a cohort of 441 children and young adults with incident epilepsy.…”
Section: Discussionsupporting
confidence: 85%
“…Out of few studies done to know the seizures' gender predominance in our country, Hakimi et al, [10] in 2013, showed the ratio of M: F -61:39 where the results are close to this study result. Maher Arabi et al [11] found, in a total of 101 patients who were studied with history of seizure 57% were male and 43% of them were female, which is very similar to this study.…”
Section: Gender Distributionsupporting
confidence: 90%
“…But in a study of 101 seizure patients, done by Maher Arabi et al[11], patients presented with a single episode seizure while 45 patients experienced more than one episode seizure.…”
mentioning
confidence: 99%
“…These findings supporting a higher incidence of NCSE in the brain areas most vulnerable to the increased production of proteins associated with Alzheimer’s disease and with neurodegeneration [16]. Also, the involvement of previous cerebral ischemic infarction in Case 2 may have accelerated epileptogenic activities [12], although the relationship with Alzheimer’s disease-associated parietal areas remains unclear.…”
Section: Discussionmentioning
confidence: 97%
“…DWI showed slightly increased abnormal signal intensity around the right parietal cortex (Figure 2A, 2B). ASL showed hyperperfusion in the right inferior parietal lobe and precuneus area of the superior parietal lobe (Figure 2C, upper panel), which correlated well with hypoperfused brain areas associated with degenerative changes in Alzheimer’s disease [10], and cortical involvement by a small ischemic lesion as a cause of post-stroke epilepsy [12]. No remarkable findings were demonstrated by MRA (Figure 2D).…”
Section: Case Reportsmentioning
confidence: 99%